An Effective Hybrid Synthesis Strategy of Multibeam Subarray - Gong, Yu; Xiao, Shaoqiu; Zheng, Yu; Wang, Bingzhong (IEEE transactions on antennas and propagation, 2022)
In this article, an effective hybrid method is proposed to design the subarrays generating multiple functional beams. In the process of synthesis, one of the target patterns is selected as the primary pattern which is generated at the element level. Other secondary patterns are generated at the subarray level by dividing the elements into nonoverlapped subarrays and utilizing attenuators and phase shifters at the subarray outputs. To simplify the complexity of the feed network, the subarray configurations of secondary patterns are the same. The proposed method consists of two steps. In the first step, the subarray configuration of the phased array is optimized by the K -means clustering method. In the second step, the convex optimization method is applied to acquiring the complex weighting coefficients of subarrays, which can improve the accuracy of the synthesized secondary patterns. A series of numerical examples demonstrate the effectiveness of the proposed method.